Exploring Performance Accountability in Practice: A Phenomenological Approach - Nikki Lare Bagoes; Novita Weningtyas Respati (Universitas Muhammadiyah Sidoarjo, 2026)
General background: Accountability is a key principle that ensures every action can be justified. Specific background: In 2023, the SAKIP assessment at the South Kalimantan Land Office of the Ministry of ATR/BPN recorded a decline compared to the previous year, raising the need to identify its causes. Knowledge gap: Existing research provides limited frameworks to explain recurring government performance issues and rarely examines accountability within the latest AKIP regulation, Permen PANRB No. 88/2021. Objective: This research explores the development of SAKIP within that regulation to understand the reality versus the ideal of AKIP. Methods: Using a qualitative phenomenological method with interviews and document analysis. Results: This study identified key barriers as misalignment between programs and strategic plans, lack of appreciation, and human resource qualifications that do not align with the required educational background. Novelty: The study contributes by applying a phenomenological perspective based on Regulation No. 88/2021, revealing methodological and contextual insights for accountability reform. Implications: It highlights that performance reports serve as a core expression of accountability, while also exposing the gap between the ideals of AKIP and their implementation on the ground